Tectonics Recent Advances - Sharkov, Evgenii (IntechOpen, 2012)
This book is devoted to different aspects of tectonic researches, especially to modern geodynamic processes. Syntheses of recent and earlier works, combined with new results and interpretations, are presented here for diverse tectonic settings. Most of chapters include up-to-date materials of detailed geological-geophysical investigations, which can help more clearly understand the essence of mechanisms of different tectonic processes. Among general problems of tectonics are discussed processes in axes of slow-spreading mid-ocean ridges on example of central part of Mid-Atlantic Ridge and in continental collision zones. Formation of sedimentary basins are considered on examples of Niger Delta, Triassic Cuyana Basin (Argentina), and Mesozoic and Cenozoic basins of the Alpine margin (Tunisia); neotectonic processes examined in Turkey and Morocco; tectonic evolution of the southern margin of Laurasia in the Paleozoic discussed as well as interrelation of western Troms-Lofoten and the Lewisian complexes in the Midle Paleoproterozoic.